Buddhist Charities and China's Social Policy. An Opportunity for Alternate Civility? - Laliberté, André (Archives de sciences sociales des religions, 2012)
Les institutions bouddhistes chinoises représentent-elles une source de sociabilité nouvelle pouvant favoriser une évolution vers un système politique plus ouvert ? On peut y répondre dans une perspective comparée qui prend en compte trois domaines d'intervention où des conflits peuvent émerger entre autorités étatiques et religieuses: l'éducation, la santé, et l'aide publique. Après un survol des politiques sociales chinoises et du rôle minimal dévolu aux institutions religieuses dans leur mise en œuvre, il est fait état des actions philanthropiques des institutions bouddhistes. Celles-ci ont adopté la même prudence que leurs collègues taïwanaises: une attitude propice à la civilité, certes, mais pas un encouragement à la réforme politique.This paper explores the possibility that Chinese Buddhist institutions can represent a source of alternate civility conducive to a more open political system. The paper starts to explore the issue from a comparative perspective and considers three area of contention between the state and religious authorities in which the latter can advance the interests of society: education, health care, and relief. After a brief survey of social policies and the role granted by the state to religious institutions as providers of services in recent years, the essay considers the philanthropic activities of Buddhist institutions. This survey looks at some of their achievements and their shortcomings, and notes that they have adopted the same cautious attitude as their co-religionists in Taiwan, which may nurture an alternate civility, but does not sustain necessarily political reform.